AraC-based pharmacotherapy of chronic myeloid leukaemia - Reiter, Andreas; Hochhaus, Andreas; Berger, Ute; Kuhn, Christian; Hehlmann, Rüdiger (Expert opinion on pharmacotherapy, 2001)
In interferon-α (IFN) treated chronic phase chronic myeloid leukaemia (CML) patients, survival depends on individual risk profile and achievement of a complete haematological response (CHR) and a major cytogenetic response (MCR) (< 35% Philadelphia-chromosome-positive metaphases). The highest cytogenetic response rates have been achieved with the combination of IFN and low-dose sc. AraC (10 mg daily to 10 - 20 mg/m2 for 10 - 14 days/month). Whether the higher cytogenetic response rates are also associated with a significant improvement of survival still remains controversial. The different results obtained from large randomised and observational trials may be due to the numbers of patients enrolled, distribution of risk profiles and the treatment schedule, which is influenced greatly by the haematological and gastrointestinal toxicity of AraC. An oral formulation (YNK01), which is lipophilic and resistant to deamination, is currently under investigation. Clinically, it has similar activity, but toxicity leads to discontinuation of treatment in a considerable proportion of patients. The clinical benefits may therefore be outweighed by the dose-limiting toxicity for both application forms. Combinations with other drugs, e.g., STI571 or homoharringtonine, have shown promising early results in vitro and in vivo.